The Physical Properties Characteristics of Laminated Board of Jackfruit, Mahogany, and Petung Bamboo - Amin, Radjali; Wulandari, Febriana Tri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Wood laminates offer a luxurious appearance and beautiful ornamental value. Petung bamboo has a very good material to be applied into laminated boards, besides the sturdy stem wall, the bamboo has a long life and is free from pests and diseases. The purpose of this study was to identify the strength class of laminated boards for construction use by analyzing the effect of the combination of jackfruit mahon wood with petung bamboo. The study showed that there was no significant difference in the strength of solid and laminated boards. The mahogany (Swietenia mahagoni L. Jacq.) and jackfruit (Artocarpus heterophyllus Lamk.) woods have medium specific gravity (0.53-0.72 for mahogany and 0.51-0.58 for jackfruit) and strength class II-III, which makes them suitable for laminated boards. The combination significantly impacts density and moisture content, but has no impact on expansion or shrinkage. Each physical examination complies with JAS SE-7 2003. This laminated board combination is classified as strength class III and is suitable for use as a building material.